2019
DOI: 10.1155/2019/1512969
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Macrophages in the Maintenance of Intestinal Homeostasis

Abstract: Intestinal macrophages constitute the largest pool of macrophages in the body and have emerged as crucial sentinels for pathogen recognition and elimination. The source and development of intestinal macrophages, as well as their distinct properties have been well documented. Intestinal macrophages exert their functions in the maintenance of intestinal homeostasis by shaping host-microbiota symbiosis, managing gut inflammation, crosstalking with T cells, and facilitating wound repair. Recently, nutritional regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 78 publications
1
51
0
1
Order By: Relevance
“…In addition, other innate effector cells such as eosinophils are produced by Ly6C hi monocytes through secretion of CCL11 (eotaxin). More importantly, Ly6C hi monocytes are reported to directly regulate the pathogenic effects of neutrophils and the production of TNF-α and reactive oxygen species (ROS) by neutrophils in a PGE2-dependent manner [88]. Excessive accumulation of lipid-laden foam cells in endothelium signifies the earliest manifestation of an atherosclerotic lesion ( Figure 5).…”
Section: Mcp-1: a Biochemical Marker Associated With Endothelial Dysfmentioning
confidence: 99%
“…In addition, other innate effector cells such as eosinophils are produced by Ly6C hi monocytes through secretion of CCL11 (eotaxin). More importantly, Ly6C hi monocytes are reported to directly regulate the pathogenic effects of neutrophils and the production of TNF-α and reactive oxygen species (ROS) by neutrophils in a PGE2-dependent manner [88]. Excessive accumulation of lipid-laden foam cells in endothelium signifies the earliest manifestation of an atherosclerotic lesion ( Figure 5).…”
Section: Mcp-1: a Biochemical Marker Associated With Endothelial Dysfmentioning
confidence: 99%
“…Dysregulated homeostasis of immune cells is associated with intestinal inflammation [8]. Of the several immune cells that regulate inflammatory responses, macrophages are important during the development of intestinal inflammation [9][10][11]. Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are inflammatory disorders that affect the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal macrophages are considered to be the main participants in establishing and maintaining gut homeostasis 4 , 70 and are important scavengers of dead and dying cells 70 . An increasing number of studies have shown that macrophages are novel potential targets for the development of new treatment approaches for IBD 4 , 6 . Thus, it is believed that understanding how apoptotic cell-engulfing macrophages promote the proliferation of epithelial cells (and thus contribute to tissue homeostasis) during IBD is believed to be critical for developing therapeutic strategies to cure such diseases 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract caused by impairment of the intestinal epithelial cell (IEC) layers 1 3 . Increasing evidence suggests that macrophages have protective functions in intestinal health and disease 4 6 . Macrophages engulf apoptotic cells that were produced by tissue damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation